Developing the Immune Defender Board Game to Enhance Students' Learning Outcomes on the Human Immune System - Fadillah Rizky Rahmawan; Shefa Dwijayanti Ramadani; Serafica Btari Christiyani Kusumaningrum; Deny Setiawan (Journal of Educational Sciences, 2026)
The material of the human immune system is abstract and complex, making it difficult for students to understand, especially when instruction is still dominated by conventional, less interactive methods, thereby affecting learning outcomes. The purpose of this study is to develop and test the effectiveness of game-based learning media using the board game Immune Defender in improving learning outcomes. This study employed the ADDIE research and development (R&D) model, with limited testing using a one-group pretest-posttest pre-experimental design. The research was conducted at SMA Negeri 1 Banjarharjo, with 32 students as research subjects. The Immune Defender media is implemented through collaborative group learning, in which students interact with challenge cards, quizzes, pathogens, and boosters that represent immune system dynamics, thereby encouraging discussion and decision-making, and reinforcing students' conceptual understanding. The results of the development of the Immune Defender board game are considered highly feasible based on assessments by material experts (90) and media experts (84.96). The implementation of this media in learning also showed a significant increase in learning outcomes (p = 0.000 < 0.05). Immune Defender media can be an alternative biology learning media that fosters a more interactive, contextual, and student-centered learning environment, thereby improving student learning outcomes in immune system materials.